Detection of Human Cytomegalovirus pp67 Late Gene Transcripts in Cerebrospinal Fluid of Human Immunodeficiency Virus Type 1-Infected Patients by Nucleic Acid Sequence-Based Amplification - Zhang, Fan (American Society for Microbiology, 2000)
This study examined the clinical correlation between the presence of human cytomegalovirus (HCMV) pp67 mRNA in cerebrospinal fluid (CSF) and active HCMV central nervous system (CNS) disease in patients with human immunodeficiency virus type 1 (HIV-1). In total, 76 CSF specimens collected from 65 HIV-1-positive patients diagnosed with HCMV CNS disease, other non-HCMV-related CNS diseases, or no CNS disease were tested for the presence of HCMV pp67 mRNA using the NucliSens cytomegalovirus (CMV) pp67 assay (Organon Teknika, Durham, N.C.). The results were compared to those of a nested PCR for the detection of HCMV glycoprotein B DNA and to those obtained by viral culture (54 samples). CSF specimens collected from patients without HCMV CNS disease yielded the following results: pp67 assay negative, 62 of 62 specimens; culture negative, 41 of 41 specimens; and PCR negative, 56 of 62 specimens (6 specimens were positive). CSF specimens collected from patients with HCMV CNS disease yielded the following results: pp67 assay positive, 9 of 13 specimens; PCR positive, 13 of 13 specimens; and culture positive, 2 of 13 specimens. After resolution of the discordant results, the following positive and negative predictive values (PPV and NPV, respectively) for the diagnosis of HCMV CNS disease were determined. The PPV for PCR, pp67 assay, and culture were 68.4, 100, and 100%, respectively, and the NPV for PCR, pp67 assay, and culture were 100, 97.0, and 82.7%, respectively. The sensitivities for DNA PCR, pp67 assay, and culture for the detection of HCMV were 100, 84.6, and 18%, respectively, and the clinical specificities were 90.5, 100, and 100%, respectively. This study indicates that the detection of HCMV pp67 mRNA in CSF has good correlation with active HCMV CNS disease, whereas CSF culture is insensitive and qualitative DNA PCR may detect latent nonreplicating virus in CSF from patients without HCMV CNS disease.